A dinâmica das teorias epistemológicas de Popper e Kuhn : o progresso da ciência no horizonte da teoria evolucionista darwiniana - Valdirlen do Nascimento Loyolla (2017)
In this thesis we aim to examine the epistemological perspectives of Karl Popper and Thomas Kuhn on the progress of scientific theories in order to analyze their metaphorical or analogical understandings of Darwin's 'natural selection theory' and what the consequences, limits and problems from the theoretical evolutionary adoption to a correct understanding of the development of science. Our comparative analysis seeks to point out which of the two epistemological approaches has a greater reach as an explanatory mechanism for the progress of scientific knowledge in contemporary times, since both Popper – in his teleological adoption of theory – and Kuhn – in his non teleological approach – take as analogical or metaphorical reference the same theoretical framework, that is, the Darwinian evolutionist theory. That problem lies on the fact that Popper's methodology in characterizing the progress of knowledge in a teleological way regarding the truth meta oriented the purpose or the determination of science, his perspective is opposed not only to Kuhn's but radically that of Darwin himself who explained natural processes as non-teleological or non-finalist dynamics of species modifications. Consequently, with the focus on the Darwinian conception that if there is no teleology or progressive march towards a final purpose in Nature, we must investigate whether in human knowledge, fundamentally in scientific knowledge, there would also be teleological progress – this seems to us to be the crux in which Popper's 'evolutionary epistemology' holds its strongest clash with Kuhn's late epistemology.